Industry 4.0 Developments towards the Fourth Industrial Revolution - Kumar, Kaushik; Zindani, Divya; Davim, J. Paulo; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book provides an overview of the burgeoning next generation of industry- Industry 4.0, which promises to increase flexibility in manufacturing in tandem with mass communication, improved productivity and better quality. This volume provides a comprehensive and holistic overview of intelligent manufacturing, process planning, assessment of product development opportunities, aspects of risk management, education and qualification requirements, socio-technical considerations and the sustainability of business models. This volume will be of interest to engineers, entrepreneurs, academics and students working in these fields. .
Chapter 1: Intelligent Manufacturing -- Chapter 2: Process Planning in Era 4.0 -- Chapter 3: Requirements of Education and Qualification -- Chapter 4: Risk Management Implementation -- Chapter 5: Socio Economic Considerations -- Chapter 6: Sustainable Business Scenarios in 4.0 Era.
Keywords: Manufactures; Industrial Management; Computer-aided engineering; Electronic circuits; Business information services; Production management; Machines, Tools, Processes; Industrial Management; Computer-Aided Engineering (CAD, CAE) and Design; Electronic Circuits and Systems; IT in Business; Operations Management